Survey of transfusion practices in preterm infants in Europe - Scrivens, A; Riebel, NJ; Heeger, L; Stanworth, S; Lopriore, E; New, HV; Dame, C; Fijnvandraat, K; Deschmann, E; Aguar, M; Braekke, K; Cardona, FS; et al. (BMJ Publishing Group, 2023)
Background Preterm infants commonly receive red blood cell (RBC), platelet and fresh frozen plasma (FFP) transfusions. The aim of this Neonatal Transfusion Network survey was to describe current transfusion practices in Europe and to compare our findings to three recent randomised controlled trials to understand how clinical practice relates to the trial data. Methods From October to December 2020, we performed an online survey among 597 neonatal intensive care units (NICUs) caring for infants with a gestational age (GA) of <32 weeks in 18 European countries. Results Responses from 343 NICUs (response rate: 57%) are presented and showed substantial variation in clinical practice. For RBC transfusions, 70% of NICUs transfused at thresholds above the restrictive thresholds tested in the recent trials and 22% below the restrictive thresholds. For platelet transfusions, 57% of NICUs transfused at platelet count thresholds above 25×109/L in non-bleeding infants of GA of <28 weeks, while the 25×109/L threshold was associated with a lower risk of harm in a recent trial. FFP transfusions were administered for coagulopathy without active bleeding in 39% and for hypotension in 25% of NICUs. Transfusion volume, duration and rate varied by factors up to several folds between NICUs.